ISLAMIC CORPORATE SOCIAL RESPONSIBILITY (ICSR); KAJIAN TEORITIS - Wahyuddin, Wahyuddin (JURNAL EKONOMI DAN BISNIS ISLAM, 2016)
Abstract.Company social caring issue has become an important record in Islamic Corporate Social Responsibility (ICSR). In Islam, the issue of social welfare and CSR environment is a very serious attention because it is one of the way to attain the goal of Islamic economy which are economic welfare, justice, equitable income distribution and individual freedom in terms of social welfare. In the implementation of CSR, maslahah and maqasid al- Shari?ah is one of the basic for falah fiddunya wal akhirat. This study will examine CSR in the theory of Islamic economy. ICSR required al-dharuriyat as the priority in this study, then al-hajjiyah and al-tahsiniyah. ICSR can be divided into three concept: spirituality concept, Rahmatan Lil?Alamin, and Ukhuwah Islamiyah. Key Words: ICSR, Islam, Social, Islamic Economy